Deaf in America : voices from a culture - Padden, Carol; Humphries, Tom (Cambridge : Harvard university press, 1988)
Met lit. opg.; reg.
Keywords: Deaf -- United States; KVHA:American Studies; KVHA:Cultuurgeschiedenis; Amerikaanse gebarentaal